Epigallocatechin-3-Gallate Protects against Homocysteine-Induced Brain Damage in Rats - Wang, Lili; Tian, Xuan (Planta Medica, 2018)
High levels of homocysteine are implicated in many neurovascular and neurodegeneration diseases. Epigallocatechin 3-gallate (EGCG), one of green tea polyphenols, has potential anti-oxidative and anti-inflammatory activities. However, it has not been explored whether EGCG has an effect on homocysteine-induced neuro-inflammation and neurodegeneration. In this study, we investigated the effects of EGCG on memory deficit, oxidative stress, neuro-inflammation, and neurodegeneration in hyper-homocysteinemic rats after a 2 wk homocysteine injection by vena caudalis. We found that supplementation of EGCG could rescue deficit of spatial memory induced by homocysteine. Treatment of EGCG significantly reduced the expression of malondialdehyde, glial fibrillary acidic protein, tumor necrosis factor-α, and interleukin-1β and increased glutathione level in the homocysteine-treated group. In TdT-mediated dUTP nick end labeling (TUNEL) assay and Fluoro-Jade B staining, supplementation of EGCG could attenuate the apoptotic neurons and neurodegeneration. Interestingly, EGCG significantly ameliorated homocysteine-induced cerebrovascular injury. Our data suggest that EGCG could be a promising candidate for arresting homocysteine-induced neurodegeneration and neuro-inflammation in the brain.
Keywords: epigallocatechin 3-gallate; oxidative stress; neuroinflammation; neurodegeneration